Relayout on the IKM Krupuk Production Section - Eko Budi Prasetyo; Atika Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2021)
This industry, established since 2009, is one of the industries for making raw crackers with various kinds of crackers, which is located in simo angin-angin village, sidoarjo city which produces various kinds of crackers, namely casandra crackers, rose crackers, braid crackers and made with quality flour and fuel. to oven, namely with the steam obtained from the boiler / steam boiler. This study aims to design and suggest improvements to the facility layout properly and the flow of materials smoothly, so that the material travel distance is not too long and can reduce the alternating flow of the production process material in CV Andi Jaya with the Activity Relation Chart method with the application blocplan. One indicator that can determine how good a Layout is is by comparing the total moments in the Layout. From the results of the calculation of total moment efficiency using BLOCPLAN shows better results, where there is an increase of 0.52% from the existing condition or initial layout.